Social Question and Professional Intervention by Social Workers - Ferreira, José Wesley (Textos & Contextos (Porto Alegre), 2010)
This article is a result of a master’s dissertation based on a qualitative research project conducted with six social workers involved in various socio-occupational contexts in the city of Porto Alegre. The study’s results reveal a theoretical weakness in the understanding of the social question and a reduction of instrumentality to the use of instruments during professional intervention. The theoretical weakness becomes evident in the difficulty of linking the expressions of the social question with their common generating axis, in an economicistic reductionism and in the appropriation of the institutional object as if it were the professional object itself. The reduction of instrumentality to the use of instruments becomes evident in the fragile association of the theoretical-methodological and technical-operational dimensions during their interventions.